WORK LIFE BALANCE MEMEDIASI ORGANIZATION CULTURE, TRI HITA KARANA PADA KINERJA KARYAWAN - I Ketut Ady Merta Antara (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to determine role of work life balance mediating influence of organization culture and Tri Hita Karana concept on employee performance. The research method is a quantitative approach with a sample of 145 people from the purposive sampling technique. Data collection through observation, interviews, literature studies, documentation and questionnaires. Quantitative descriptive analysis techniques and Partial Least Square with the Structural Equation Modeling. The results of the study indicate that 1) organization culture has a positive and significant effect on employee performance of 2.016. 2) organization culture has a positive and significant effect on work life balance of 3.195. 3) Tri Hita Karana concept has a positive and significant effect on employee performance of 3.848. 4) Tri Hita Karana concept has a positive and significant effect on work life balance of 5.396. 5) work life balance has a positive and significant effect on employee performance of 3.447. 6) work life balance plays a positive and significant role in mediating the influence of organization culture on employee performance of 2.720. 7) work life balance plays a positive and significant role in mediating the influence of the Tri Hita Karana concept on employee performance 2,500.